A 3D Simulation of a Moving Solid in Viscous Free-Surface Flows by Coupling SPH and DEM. (10th January 2017) - Qiu, Liu-Chao; Liu, Yi; Han, Yu
Abstract : This work presents a three-dimensional two-way coupled method to simulate moving solids in viscous free-surface flows. The fluid flows are solved by weakly compressible smoothed particle hydrodynamics (SPH) and the displacement and rotation of the solids are calculated using the multisphere discrete element method (DEM) allowing for the contact mechanics theories to be used in arbitrarily shaped solids. The fluid and the solid phases are coupled through Newton's third law of motion. The proposed method does not require a computational mesh, nor does it rely on empirical models to couple the fluid and solid phases. To verify the numerical model, the floating and sinking processes of a rectangular block in a water tank are simulated, and the numerical results are compared with experimental results reported in published literatures. The results indicate that the method presented in this paper is accurate and is capable of modelling fluid-solid interactions with a free-surface.